2021
DOI: 10.5713/ajas.20.0031
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment interaction for somatic cell score in Holstein cattle of southern Brazil via reaction norms

Abstract: Objective: The objective of this study was to evaluate the genetic behavior of a population of Holstein cattle in response to the variation of environmental temperature by analyzing the effects of genotype by environment interaction (GEI) through reaction norms for the somatic cell score (SCS).Methods: Data was collected for 67,206 primiparous cows from the database of the Paraná Holstein Breeders Association in Brazil, with the aim of evaluating the temperature effect, considered as an environmental variable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Except for the beginning of lactation, the increasing permanent environmental variance during lactation indicates the importance of non-genetic factors on SCS. The results of this study, similar to other studies (Koivula et al 2005;Mulim et al 2021), revealed that SCS is strongly affected by the temporary environmental variance.…”
Section: Variances and Heritabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Except for the beginning of lactation, the increasing permanent environmental variance during lactation indicates the importance of non-genetic factors on SCS. The results of this study, similar to other studies (Koivula et al 2005;Mulim et al 2021), revealed that SCS is strongly affected by the temporary environmental variance.…”
Section: Variances and Heritabilitysupporting
confidence: 92%
“…A reason for the existence of G × E interaction and low genetic correlation between the moderate and cold climate is the influence of environmental effects on this trait especially in early lactation. Mulim et al (2021) Ismael et al (2016) concluded that genetic correlations of time from calving to first insemination were close to unity, indicating no genotype by environment interaction between different geographic locations. On the other hand, genetic correlations less than unity were reported between calving seasons for days open in the US Holstein cows (Oseni et al 2004) and for age at first calving between Brazil and Colombia (Ceron-Munoz et al 2004).…”
Section: Genotype By Environment Interactionmentioning
confidence: 99%
“…The degree of reranking of bulls is a widespread criterion to establish if the introduction of GxE is useful for routine selection practice or not: e.g., minor reranking of bulls for fat and protein yield [ 80 ] and for SCS [ 27 ] was observed in Brazilian Holstein bulls, suggesting non-relevant GxE. Despite a higher genetic response under intensive herd management, no reranking was found in French Holstein, Normande and Montbéliarde, despite a higher genetic response under intensive herd management [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have considered climate characteristics such as temperature-humidity variation as an environmental covariate in modelling (e.g., [ 24 ]), but other conditions such as herd management (e.g., [ 25 ]) or average production level (e.g., [ 26 ]) can also be considered. Reaction norm can be modelled using a single-step or two step analysis: the first is generally used when a climatic descriptor such as temperature or the temperature-humidity index (THI) is directly used as an environmental covariate [ 8 , 24 , 27 ], whereas a two-steps model is applied when herds of similar conditions (often called contemporary groups) are considered as an environmental gradient [ 11 , 28 , 29 ]. This last form of modelling is particularly useful when various geographical and farm-management conditions characterize the rearing systems in a breed, such as in Brown Swiss of Germany and Austria [ 10 ], and Rendena [ 30 ], which is the study subject.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gerber et al [31], Huquet et al [32], Calus et al [21], and Schmid et al [33] studied macro-environmental plasticity for production traits in German Simmental, French Holstein, Dutch Holstein Friesian cattle, and German Brown Swiss cattle, defining the environmental conditions with different management parameters. Similarly, Santos et al [34] and Mulim et al [35,36] studied production traits in Brazilian Holstein, and Bohlouli et al [37] studied production traits as well as milk fat composition in German Holstein.…”
Section: Studies That Aimed At Estimating Gxe For Economically Releva...mentioning
confidence: 99%